Mothers : a novel - Lozano, Brenda, 1981- (Catapult, 2025)
"When the kidnapping of a little girl shocks the Mexican capital, the lives of two very different women become forever intertwined. Gloria Felipe lives a comfortable upper-class life with her husband and five children. Nuria Valencia comes from a working-class background and has been desperately trying to get pregnant in order to save her marriage. After traditional methods produce no results, she subjects herself to horrific fertility treatments designed and administered by men, and ultimately tries to adopt but is rejected on the basis that a woman in her early thirties is too old to adopt a baby. Failed time and again by the system and about to lose hope, she is presented with an opportunity that seems almost too good to be true. Through the eyes of a wry unnamed narrator, we witness the battle of the Felipe family to recover their youngest member and the anguished attempts of the Valencia family to save their daughter from potential danger." --